Study Of Bearing Capacity Of Piles Due To Vertical Loading In Pontianak - Saputra, Nanda Zulna; Bachtiar, Vivi; Priadi, Eka (Fakultas Teknik Universitas Tanjungpura, 2025)
Infrastructure development in Pontianak, particularly the Kapuas Bridge Duplication Project 1 (MYC) 2022-2024, requires thorough foundation planning due to the area